Can food-based strategies help reduce vitamin A and iron deficiencies? a review of recent evidence - Ruel, Marie T. (International Food Policy Research Institute, 2001)
Micronutrient malnutrition is still a problem of unacceptable proportions in developing countries. Iron and vitamin A deficiencies are the most widespread nutrition deficiencies in the world today, affecting perhaps as many as 3.5 billion people..... Food-based approaches are essential to the fight against micronutrient deficiencies. Of all the strategies, they probably require the highest level of initial investment, but they are also the only ones that hold a promise of sustainability. The evidence presented in this Food Policy Review highlights the key role of education in ensuring the success of food-based approaches. Changing people’s behavior in terms of the foods they grow and eat and how they prepare and process them requires a significant amount of effort. It is, however, the only way to enable people to take ultimate responsibility for the quality of their diet. (from Foreword by Per Pinstrup-Andersen